The Competing Effects of Breaking Waves on Surfzone Heat Fluxes: Albedo Versus Wave Heating. Issue 10 (9th October 2018) - Sinnett, Gregory; Feddersen, Falk
Abstract: Depth‐limited wave breaking modifies the heat flux in the surfzone relative to the inner‐shelf (where waves are not breaking). Surfzone wave breaking generates heat through viscous dissipation (wave heating), but also increases surface foam coverage and albedo, thereby reducing solar heating, that is, cooling relative to the inner‐shelf. These two competing breaking wave effects are quantified with a yearlong experiment at the Scripps Institution of Oceanography Pier. Cross‐shore averaged surfzone albedo estimates were more than three times higher than inner‐shelf albedo, reducing the yearly averaged surfzone water‐entering shortwave radiation by 41 W/m 2 relative to the inner‐shelf. Surfzone breaking wave dissipation added an additional yearly averaged 28 W/m 2 relative to the inner‐shelf. The albedo‐induced solar heating reduction in spring, summer, and fall was usually greater than the wave heating. However, in winter, large waves and relatively weak shortwave solar radiation (due to both lower top of the atmosphere solar radiation and clouds) resulted in a nearly equal number of days of breaking wave‐induced heating or cooling. These two heat flux terms are coupled via wave breaking dissipation. Averaged over the surfzone, the albedo‐induced solar radiation reduction is linearly related to the downwelling solar radiation and is independent of wave height. Consequently, the albedo‐induced cooling to wave heating ratio is a function of breaking wave height to the −3/2 power, allowing evaluation of the relative importance of these terms in other geographic regions. Plain Language Summary: Temperature variation in nearshore waters affects the local ecology, and is also used to study important physical processes. Wave breaking contributes to surfzone temperature variation in two ways. First, breaking waves dissipate their energy in the surfzone creating friction (heat) and foam. Surfzone foam reflects sunlight reducing solar warming of the surfzone, thus leading to cooling relative to no wave breaking. These two competing wave effects (addition of frictional heating and reduction in solar heating) are quantified with a yearlong experiment at the Scripps Institution of Oceanography pier (La Jolla, CA). On average, frictional wave heating added 28 W to each square meter of surfzone. At the same time, surface foam reduced the solar heating in each square meter of surfzone by 41 W on average. The relative contribution of these competing effects varied depending on the wave height and the available sunlight, which depended on seasons and clouds. Temperature variation caused by these two effects can be estimated at other locations if the wave height and the amount of sunlight are known. Key Points: Surfzone breaking waves heat via dissipation; foam increases albedo, reducing solar radiation Over a year, the albedo‐induced solar heating reduction was most significant The net effect depends on incident wave height, latitude, seasons, beach slope, and cloudiness